Pengaruh Kompetensi Karyawan, Lingkungan Fisik, dan Promosi terhadap Kepuasan Pengunjung Menginap di Hotel Le Polonia Medan - Rangkuti, Dhita Adriani; Ali, Kevin; Harjen, Justin (Universitas Batanghari Jambi, 2024)
Hotel Le Polonia is a hotel located in an urban area in the city of Medan. This hotel began operating in 1977 with a total of 51 rooms at that time. By offering a classic concept and providing good facilities and comfort for hotel visitors. Currently, the types of rooms offered by Hotel Le Polonia are superior deluxe, family room, premier deluxe, junior suite and polonia suite. This research uses quantitative descriptive research methods. The sample in the study was 110 samples. The results of this research show that the sig value for influencing employee competence on visitor satisfaction is 0.19 < 0.05 and the t-count value is 2,376 < t-table 1,983. The sig value for influencing the physical environment on visitor satisfaction is 0.045 < 0.05 and the t-count value is 2.033 > t-table 1.983. The sig value for influencing promotions on visitor satisfaction is 0.014 < 0.05 and the t-count value is 2,500 > t-table 1.983; It can be concluded that partially the variables of employee competency, physical environment and promotion have a positive and significant effect on visitor satisfaction at the Le Polonia Hotel Medan. F-count value 5.579 > F-table 2.69; This indicates that there is an influence of employee competence, physical environment, and promotion simultaneously on visitor satisfaction at Hotel Le Polonia.